1986
DOI: 10.1073/pnas.83.16.6203
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic control of 125I-labeled neurotensin binding site density in corticolimbic structures of the rat brain.

Abstract: In the rat brain, destruction of dopaminergic cell groups by injections of 6-hydroxydopamine into the ventral mesencephalic tegmentum results in large decreases in the number of neurotensin binding sites in the mesencephalon and the striatum. In contrast, these lesions produce an increase in the number of 1251-labeled neurotensin binding sites in the lateral part of the prefrontal cortex despite a large decrease in cortical dopamine levels. Increases; in the number of 125I-labeled neurotensin binding sites in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(27 citation statements)
references
References 40 publications
(40 reference statements)
5
22
0
Order By: Relevance
“…Finally, SR 48692 was even more potent than unlabeled neurotensin in binding to guinea pig brain tissues as shown by both radioreceptor assay and autoradiographic techniques. Consistent with the existence of neurotensin binding sites on terminals of the nigrostriatal dopaminergic pathway (29,30), neurotensin was shown to promote an increase in K+-evoked release of [3H]dopamine from rat, cat, and rabbit striatal slices (31)(32)(33). This observation was extended here to guinea pig striatal slices.…”
Section: Pre~ara~on Of Timm S Whole Brain Homoge-supporting
confidence: 69%
“…Finally, SR 48692 was even more potent than unlabeled neurotensin in binding to guinea pig brain tissues as shown by both radioreceptor assay and autoradiographic techniques. Consistent with the existence of neurotensin binding sites on terminals of the nigrostriatal dopaminergic pathway (29,30), neurotensin was shown to promote an increase in K+-evoked release of [3H]dopamine from rat, cat, and rabbit striatal slices (31)(32)(33). This observation was extended here to guinea pig striatal slices.…”
Section: Pre~ara~on Of Timm S Whole Brain Homoge-supporting
confidence: 69%
“…For example, unilateral striatal lesions which destroyed a certain proportion of dopaminergic terminals in the lesioned striatum led to slight, but significant, increase of neurotensin-binding site densities in the contralateral striatum [35] . Furthermore, in bilateral 6-OHDA-lesioned rats, the number of neurotensin-binding sites was increased in the lateral part of the prefrontal cortex [36] . However, Masuo et al [37] reported that there was no significant change of neurotensin receptors in the contralateral striatum and substantia nigra of 6-OHDA-lesioned rats, although the expression on contralateral striatum and substantia nigra was much higher than that on the lesioned side.…”
Section: Discussionmentioning
confidence: 99%
“…Lesioning studies in the striatum with 6-hydroxy dopamine have demonstrated that there is a close link between dopamine and NT receptor function (Fuxe et al, 1986), whereby striatal lesions produced similar alterations in NT receptor function to administration of chronic haloperidol in the present study. Herve et al (1986) have demonstrated previously that destruction of dopamine cell groups using 6-hydroxydopamine lesions results in decreased numbers of NT binding sites in the striatum and mesencephalon. Furthermore, when the long-acting neuroleptic, pipotiazine palmitic ester was used to produce chronic blockade of dopamine neurotransmission, there was a resulting increase in the density of postsynaptic NT binding sites in the straitum (Herve et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Herve et al (1986) have demonstrated previously that destruction of dopamine cell groups using 6-hydroxydopamine lesions results in decreased numbers of NT binding sites in the striatum and mesencephalon. Furthermore, when the long-acting neuroleptic, pipotiazine palmitic ester was used to produce chronic blockade of dopamine neurotransmission, there was a resulting increase in the density of postsynaptic NT binding sites in the straitum (Herve et al, 1986). This suggests that there is a close relationship between dopamine and NT systems in the rat brain.…”
Section: Discussionmentioning
confidence: 99%